Renormalization in T T ¯ -deformed nonintegrable theories - Chakrabarti, Subhroneel; Manna, Arkajyoti; Raman, Madhusudhan [UNESP] (American Physical Society (APS), 2022)
That the exact quantum S-matrix of TT¯-deformed field theories is known has interesting consequences for their perturbative renormalization. Recent investigations into the interplay between renormalization and integrable deformations have focused on those cases where the (undeformed) seed theories are integrable. In this paper, we study the perturbative renormalization of nonintegrable TT¯-deformed field theories, focusing on a theory of scalars with a quartic interaction. We show that in this theory, the 4-point 1-loop S-matrix exhibits features similar to its integrable cousins. We also carry out a similar analysis for the case of an integrable quantum field theory comprising a pair of chiral bosons. Our discussion of this latter theory supplies the first explicit example of a perturbative field theory computation in the formalism due to Sen.